Penerapan Model Pembelajaran Teams Games Tournament Berbatuan Media DSA untuk Meningkatkan Hasil Belajar IPA Kelas V SDN 6 Ampenan - Nurrahmi, Nurrahmi; Musaddat, Syaiful; Suryani, Nurrahma (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is motivated by the low learning outcomes in the science subject on the water cycle in Grade V. Through classroom action research conducted in two cycles, each cycle in this study went through four repeated stages: planning, implementation, observation, and reflection. The researcher aimed to improve the quality of students' learning outcomes on the water cycle material for Grade V students at SDN 6 Ampenan, involving 33 student participants, by applying the TGT (Teams Games Tournament) model and DSA media. This study indicates that, out of a total of 33 Grade V students, 10 students (25%) initially met the Minimum Mastery Criteria (KKM), while 23 students (75%) were not yet able to meet the KKM. In Cycle I, 19 students (55%) met the KKM, while 14 students (45%) were still unable to meet it. By Cycle II, the learning outcomes of the students met the passing criteria. The application of the TGT (Teams Games Tournament) learning model, supported by DSA (Digital Simulation Aid) tools, can improve learning outcomes in the science subject on the water cycle in Grade V at SDN 6 Ampenan for the 2023/2024 academic year.